Tea Polyphenols EGCG and Theaflavin Inhibit the Activity of SARS-CoV-2 3CL-Protease In Vitro - Jang, Minsu (Evid Based Complement Alternat Med, 2020)
COVID-19, a global pandemic, has caused over 750,000 deaths worldwide as of August 2020. A vaccine or remedy for SARS-CoV-2, the virus responsible for COVID-19, is necessary to slow down the spread and lethality of COVID-19. However, there is currently no effective treatment available against SARS-CoV-2. In this report, we demonstrated that EGCG and theaflavin, the main active ingredients of green tea and black tea, respectively, are potentially effective to inhibit SARS-CoV-2 activity. Coronaviruses require the 3CL-protease for the cleavage of its polyprotein to make individual proteins functional. EGCG and theaflavin showed inhibitory activity against the SARS-CoV-2 3CL-protease in a dose-dependent manner, and the half inhibitory concentration (IC(50)) was 7.58 μg/ml for EGCG and 8.44 μg/ml for theaflavin. In addition, we did not observe any cytotoxicity for either EGCG or theaflavin at the concentrations tested up to 40 μg/ml in HEK293T cells. These results suggest that upon further study, EGCG and theaflavin can be potentially useful to treat COVID-19.